Pharmacological activities of crude methanolic extract of Nitzschia paleacea Grunow - Fantonalgo, Raymund Noble (Miag-ao, Iloilo University of the Philippines in the Visayas, 2009)
This study evaluated the pharmacological activities of the crude methanolic extract of Nitzschiapaleacea. The extract was assayed for the presence of the following activities : antimicrobial, spasmolytic, anti-inflammatory, anti-diabetic, and analgesic. Phytochemical screening was performed to test for the presence of the bioactive metabolites responsible for its pharmacological activities. Results of the study showed that the extract inhibited the growth of Bacillus subtilis at three concentrations (100, 500, and 1000 mg mL-1) tested. The growth of Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus was inhibited when the concentration of the extract was increased to 1000mg mL-1. The growth inhibition however, was not significantly equal to that of antibiotic (Amoxicillin) standard (p<0.01). The extract did not also inhibit the growth of fungus Candida albicans at any concentrationsassayed. When tested for spasmolytic activity, the extract had neither antispasmodic nor laxative properties. For anti-inflammatory activity, at a dose of 400 mg kg-1 body weight (BW), the extract reduced inflammation (37.59%), however it was significantly lower (p,0.01) than the activity of Indomethacin (74.96%) at a dose of 10 mg kg-1 BW. Fasting blood sugar assay showed that at a dose of 800 mg kg-1 BW, the extract effectively reduce the blood sugar level (48.69%) of the hyperglycemic mice in the same manner (p.0.01) as Glipizide (54.36%) did at a dose of 15 mg kg-1 BW. Tail immersion assay revealed that at a dose of 500 mg kg-1 BW, the extract had the potential to ease pain similar (p>0.01) to Mefenamic acid at a dose of 5 mg kg-1 BW. The mice toxicity assay showed that the extract was not toxic to the mice even at the highest dose (1000ppm) tested. Phytochemical screening demonstrated the presence of flavonoids in the extract which could be associated for its pharmacological activities. This diatom can be a potential source of the metabolites for analgesic and anti-diabetic drug development.
Thesis (M. S. Biology) -- Miagao, Iloilo : U. P. in the Visayas, December 2009.